Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3991/ijim.v17i03.34699
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students' Critical Thinking Skills: Is Interactive Video and Interactive Web Module Beneficial?

Abstract: This study aims to analyze the comparison of students' critical thinking skills by using learning media based on phenomenon-based learning in a general chemistry course. The media were an interactive web module and an interactive video about the colloidal system. This research is comparative research with a quantitative approach. The sample comprised 68 students from the State Islamic University of Sultan Syarif Kasim Riau and The University of Riau from the chemistry education department. The research data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 65 publications
2
10
0
1
Order By: Relevance
“…The confirmation method in question is that the researcher presented material in the form of a combination of learning and reinforcement videos by a model lecturer. The results of this research are also in line with the theory, which states that learning videos tend to be 327 Muhamad Galang Isnawan, Farah Heniati Santosa, Luthfiyati Nurafifah, Farid Gunadi, Diki Mulyana effective as a means of presenting material because they can be played repeatedly by students (Coles, 2014;Febliza et al, 2023). The results of this research are also in line with several previous studies (Naidoo & Hajaree, 2021;Santagata et al, 2021), which revealed that learning that combines learning videos and repetition of explanations by teachers tends to be able to optimize students' understanding of material.…”
Section: Retrospective Analysis/seesupporting
confidence: 84%
“…The confirmation method in question is that the researcher presented material in the form of a combination of learning and reinforcement videos by a model lecturer. The results of this research are also in line with the theory, which states that learning videos tend to be 327 Muhamad Galang Isnawan, Farah Heniati Santosa, Luthfiyati Nurafifah, Farid Gunadi, Diki Mulyana effective as a means of presenting material because they can be played repeatedly by students (Coles, 2014;Febliza et al, 2023). The results of this research are also in line with several previous studies (Naidoo & Hajaree, 2021;Santagata et al, 2021), which revealed that learning that combines learning videos and repetition of explanations by teachers tends to be able to optimize students' understanding of material.…”
Section: Retrospective Analysis/seesupporting
confidence: 84%
“…In addition, Yu (2022) demonstrated that after the COVID-19 pandemic, students' digital literacy was significantly improved. This increase occurred because, during the COVID-19 pandemic, students were forced to participate in online learning (Chawłowska et al, 2021) and used various kinds of media such as interactive video and interactive web (Febliza et al, 2023), e-book, interactive e-book and virtual laboratory (Febliza et al, 2022). Furthermore, turning to indicators shows that the average student on technology indicators, mobile phones/smartphones, social media, and online safety obtains a level of digital literacy on established criteria.…”
Section: Digital Literacy Of Pre-service Teachers By Agementioning
confidence: 99%
“…Il presente studio ha delle ovvie limitazioni, considerando che gli esempi presentati si basano solo su due esperimenti che coinvolgono un numero relativamente piccolo di studenti, ma conferma risultati che la letteratura accademica sui meme in generale e i meme matematici in particolare sta raccogliendo nel mondo, dagli Stati Uniti (Robinson & Robinson, 2021) all'Indonesia (Febliza et al, 2023). I meme matematici coinvolgono autore e lettore in un processo di cooperazione interpretativa (Eco, 1979) e raccontano idee matematiche caricandole di elementi emotivi che possono favorire l'attribuzione di un significato personale alle azioni nel processo di apprendimento (Skovsmose, 2005), introducendo «una cornice che possa sostenere le ragioni dell'apprendimento» (p. 94, traduzione dell'autrice).…”
Section: Riflessioni Conclusiveunclassified